If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13x + x = 5x + 13 Combine like terms: -13x + x = -12x -12x = 5x + 13 Reorder the terms: -12x = 13 + 5x Solving -12x = 13 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -12x + -5x = 13 + 5x + -5x Combine like terms: -12x + -5x = -17x -17x = 13 + 5x + -5x Combine like terms: 5x + -5x = 0 -17x = 13 + 0 -17x = 13 Divide each side by '-17'. x = -0.7647058824 Simplifying x = -0.7647058824
| 4w+8=24 | | -1[7x+6-7(x+1)]=-4x-6 | | w=17 | | 4x-9=3x+9 | | 17x+29y=-7 | | -4*-9=-5-6* | | -10+t=7 | | 4-2|3x=8 | | 4-2|3c=8 | | 4n+12=216 | | 3x^4+5x^3-4x^2-5x-2=0 | | -3b+9=-3b | | 4t+-5t+19t=-18 | | 13x+x=5x+34 | | 3x+7x+2+3=35 | | 7x+12=3x+48 | | 10q-4q-3q=18 | | y+2=30 | | -1|5y=20 | | 3n+3=126 | | 7x+20=3x+76 | | 7x+20+3x+76=180 | | 2x+10-5=25 | | 3x+195+5x+129=180 | | 2x+112+5x+145=180 | | 7.4r+2=-28 | | -x-4=1 | | 3(y+7)=2(y+9)-y | | 4x+2=-(8-7) | | 4(x+7)=40 | | 5.2f=36.4 | | -2(t+1)=4(1-2t) |